3D Jet Writing: Functional Microtissues Based on Tessellated Scaffold Architectures. Issue 14 (27th February 2018) - Jordahl, Jacob H.; Solorio, Luis; Sun, Hongli; Ramcharan, Stacy; Teeple, Clark B.; Haley, Henry R.; Lee, Kyung Jin; Eyster, Thomas W.; Luker, Gary D.; Krebsbach, Paul H.; Lahann, Joerg
Abstract: The advent of adaptive manufacturing techniques supports the vision of cell‐instructive materials that mimic biological tissues. 3D jet writing, a modified electrospinning process reported herein, yields 3D structures with unprecedented precision and resolution offering customizable pore geometries and scalability to over tens of centimeters. These scaffolds support the 3D expansion and differentiation of human mesenchymal stem cells in vitro. Implantation of these constructs leads to the healing of critical bone defects in vivo without exogenous growth factors. When applied as a metastatic target site in mice, circulating cancer cells home in to the osteogenic environment simulated on 3D jet writing scaffolds, despite implantation in an anatomically abnormal site. Through 3D jet writing, the formation of tessellated microtissues is demonstrated, which serve as a versatile 3D cell culture platform in a range of biomedical applications including regenerative medicine, cancer biology, and stem cell biotechnology. Abstract : Stabilized electrospun microfibers are stacked to create 3D scaffold structures to support the growth of tessellated microtissues. In vitro and in vivo applications of tessellated microtissues demonstrate the versatility of this cell–scaffold construct. Demonstrated applications from in vitro 3D cell culture, tissue regeneration, and disease tissue models are explored.